5x+2(x-3)=12x-5+14

Simple and best practice solution for 5x+2(x-3)=12x-5+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+2(x-3)=12x-5+14 equation:


Simplifying
5x + 2(x + -3) = 12x + -5 + 14

Reorder the terms:
5x + 2(-3 + x) = 12x + -5 + 14
5x + (-3 * 2 + x * 2) = 12x + -5 + 14
5x + (-6 + 2x) = 12x + -5 + 14

Reorder the terms:
-6 + 5x + 2x = 12x + -5 + 14

Combine like terms: 5x + 2x = 7x
-6 + 7x = 12x + -5 + 14

Reorder the terms:
-6 + 7x = -5 + 14 + 12x

Combine like terms: -5 + 14 = 9
-6 + 7x = 9 + 12x

Solving
-6 + 7x = 9 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
-6 + 7x + -12x = 9 + 12x + -12x

Combine like terms: 7x + -12x = -5x
-6 + -5x = 9 + 12x + -12x

Combine like terms: 12x + -12x = 0
-6 + -5x = 9 + 0
-6 + -5x = 9

Add '6' to each side of the equation.
-6 + 6 + -5x = 9 + 6

Combine like terms: -6 + 6 = 0
0 + -5x = 9 + 6
-5x = 9 + 6

Combine like terms: 9 + 6 = 15
-5x = 15

Divide each side by '-5'.
x = -3

Simplifying
x = -3

See similar equations:

| 4(2x+3)-6x=18 | | -8x-(3x+6)=44-x | | 2t(t+5)+1=3t-3-t^2 | | 4x+4+2x= | | -3x+6=-3x+9 | | 10z+4=10(z+1)-6 | | 4i(6i)=48 | | (a-2)x=a^2-4 | | x^2-4bx+3b^2-4b-4=0 | | 2x+2x+46+x+14=180 | | -6a-15=-3a-21 | | 4x=8x+3 | | 3.2h-2.4=2.4+1.2h | | 7x+8=5x+12 | | -3[-4-(65-99)]= | | 2x-4=x+7 | | x-25y=144 | | 4-6c=c+11 | | -2b-8=-2b+8 | | 3+7x=33-x | | 7(2x+8)-11x=2 | | 1=3.8x-0.9 | | 2x+5+3x+10=7x+1 | | 4(x-2)+3(-x+4)=-2(x-3) | | 3(x-4)=3x+7 | | 12x-12x-6y+6y=-12 | | 12.8-g=9.5 | | (x+9)+(5x+5)=3x+3 | | m-57=m-19 | | x+9=5x+5 | | 5x-y+4x+2y+19=160 | | 4m-57=m-19 |

Equations solver categories